Regulation of Expression of the adhE Gene, Encoding Ethanol Oxidoreductase in Escherichia coli: Transcription from a Downstream Promoter and Regulation by Fnr and RpoS - Membrillo-Hernández, Jorge (American Society for Microbiology, 1999)
The adhE gene of Escherichia coli, located at min 27 on the chromosome, encodes the bifunctional NAD-linked oxidoreductase responsible for the conversion of acetyl-coenzyme A to ethanol during fermentative growth. The expression of adhE is dependent on both transcriptional and posttranscriptional controls and is about 10-fold higher during anaerobic than during aerobic growth. Two putative transcriptional start sites have been reported: one at position −292 and the other at −188 from the translational start codon ATG. In this study we show, by using several different transcriptional and translational fusions to the lacZ gene, that both putative transcriptional start sites can be functional and each site can be redox regulated. Although both start sites are NarL repressible in the presence of nitrate, Fnr activates only the −188 start site and Fis is required for the transcription of only the −292 start site. In addition, it was discovered that RpoS activates adhE transcription at both start sites. Under all experimental conditions tested, however, only the upstream start site is active. Available evidence indicates that under those conditions, the upstream promoter region acts as a silencer of the downstream transcriptional start site. Translation of the mRNA starting at −292, but not the one starting at −188, requires RNase III. The results support the previously postulated ribosomal binding site (RBS) occlusion model, according to which RNase III cleavage is required to release the RBS from a stem-loop structure in the long transcript.